Conservation behavior over time: Examining a Midwestern farmer sample. (April 2022) - Beetstra, Margaret A.; Wilson, Robyn S.; Doidge, Mary
Abstract: Conservation practices are heavily promoted in agriculture, yet adoption rates remain low and relatively stagnant. We conducted a panel study of reported farmer subsurface placement and cover crop adoption in the Western Lake Erie Basin to assess (1) if reported adoption is changing over time, and (2) what is driving this change. Our results indicate that similar numbers of farmers are adding (~12%) and discontinuing use of (~14%) these practices. We find no evidence that prior intention increases the likelihood of future practice use, suggesting that intentions do not necessarily translate into behavior. We also examined self-efficacy (i.e., perceived control) and response efficacy (i.e., beliefs about practice effectiveness) but find limited evidence that these are changing over time and increasing adoption. The results suggest that increases in critical conservation practice adoption is not occurring, potentially because farmer efficacy, which might build stronger intentions and lead to change over time, is not increasing. Highlights: Farmer use of subsurface placement and cover crops is stagnant. For these conservation practices, the link between intentions and behavior is weak. Self- and response efficacy have a limited impact on conservation adoption.